2012
DOI: 10.1177/0093650212449353
|View full text |Cite
|
Sign up to set email alerts
|

Does It Matter Where You Read the News Story? Interaction of Incivility and News Frames in the Political Blogosphere

Abstract: The political blogosphere is replete with uncivil discussions and is apt to examine the influence of incivility on news frames. The present study brings in literature from incivility and framing effects and uses two experiments to examine the influence of incivility on news frames for democratic outcomes such as willingness to participate, online participation, openmindedness, and attitude certainty. Primary findings indicate the detrimental effects of incivility causing less openmindedness and more attitude c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 45 publications
2
105
1
7
Order By: Relevance
“…Consistent with deliberation theorists' arguments, recent studies revealed that exposure to uncivil political discourse produces negative emotions and attitudes toward the opposing side (Borah, 2014;Hwang, Borah, Namkoong, & Veenstra, 2008), suggesting that uncivil online discussion emphasizing antagonism between two partisan groups may erode individuals' expectation about reaching consensus through deliberation. Previous studies on intergroup conflict have also shown that as conflict between groups increases, group members tend to show negative perceptual biases toward out-group members (Brewer, 2007;Riek, Mania, & Gaertner, 2006) and increased inter-group differentiation (Forsyth, 1990).…”
Section: The Effects Of Incivility On Public Deliberationmentioning
confidence: 75%
See 1 more Smart Citation
“…Consistent with deliberation theorists' arguments, recent studies revealed that exposure to uncivil political discourse produces negative emotions and attitudes toward the opposing side (Borah, 2014;Hwang, Borah, Namkoong, & Veenstra, 2008), suggesting that uncivil online discussion emphasizing antagonism between two partisan groups may erode individuals' expectation about reaching consensus through deliberation. Previous studies on intergroup conflict have also shown that as conflict between groups increases, group members tend to show negative perceptual biases toward out-group members (Brewer, 2007;Riek, Mania, & Gaertner, 2006) and increased inter-group differentiation (Forsyth, 1990).…”
Section: The Effects Of Incivility On Public Deliberationmentioning
confidence: 75%
“…Based upon a common theme in the definition of incivility in prior studies (Borah, 2014;Brooks & Geer, 2007;Mutz & Reeves, 2005;Sobieraj & Berry 2011), we define incivility in political discussion as an extreme form of polarized discussion in which discussion participants use disrespectful statements or attacks which clearly demonstrate disrespect or insult toward an opposing political party or its members.…”
Section: Incivility and Political Polarizationmentioning
confidence: 99%
“…At the same time, if one believes that any reaction is better than no reaction at all, incivility might be considered a way to increase readers' involvement in the discussion (cf. Borah, ). Clicking an icon to register support or opposition is clearly a limited means of involving oneself in a discussion, but it is nonetheless a more tangible means of involvement than is doing nothing.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects of the definition adopted in this project are noteworthy. In focusing on disrespect, we align ourselves with the majority of the scholarship in this area (e.g., Anderson, Brossard, Scheufele, Xenos, & Ladwig, 2013;Borah, 2012;Carter, 1998;Papacharissi, 2004;Sapiro, 1999). As Brooks and Geer (2007) explain in reviewing different conceptualizations, "The concept of civility seems to invariably involve some notion of mutual respect" (p. 4).…”
Section: Incivility Public Discussion and The Internetmentioning
confidence: 99%
See 1 more Smart Citation